STRATEGI KEPALA SEKOLAH DALAM IMLPEMENTASI PROGRAM LITERASI MEMBACA SISWA DI SMP LABSCHOOL UNESA 3 - Putri Fitria Hidayah; Rezki Nurma Fitria; Amrozi Khamidi; Nuphanudin Nuphanudin; Kaniati Amalia (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the principal's strategy in implementing the reading literacy program at SMP Labschool UNESA 3 Surabaya using Mintzberg's 5P framework (Plan, Ploy, Pattern, Position, Perspective) and to examine its impact on students' reading habits and literacy achievement. A qualitative case study approach was employed. Data were collected through in-depth interviews with the principal, vice principal, language teacher, and four students (purposive sampling), supplemented by school documentation. Analysis followed Miles et al.'s (2014) interactive model with source triangulation. The principal's strategy spans five dimensions: (1) Plan: data-driven planning based on school quality reports and AKM results, integrated into the curriculum; (2) Ploy: differentiated reading materials, indirect teacher engagement through self-made modules, and web-based literacy journal monitoring; (3) Pattern: consistent 20 minute daily pre-lesson reading reinforced through morning assembly and P5 project integration; (4) Position: literacy identity built through library facilities, reading corners, external collaboration, and public gelar karya events; (5) Perspective: a long-term vision of literacy as a tool for intellectual development and critical thinking. National literacy scores recovered from 88.89% (2024) to 97.98% (2025), and students reported improved reading habits and comprehension. This is among the first studies to apply Mintzberg's 5P framework to analyze literacy leadership at the junior secondary school level in Indonesia.